Toxicity of Amphotericin B in Rabbit Corneal Epithelial Cells Stored in Optisol™-GS: Corneal Epithelial Cell Morphology and Migration. (2nd September 2022) - Harada, Kohei; Fukuoka, Hideki; Ban, Yuriko; Aziza, Yulia; Horiguchi, Go; Tanioka, Hidetoshi; Kinoshita, Shigeru; Uematsu, Masafumi; Kitaoka, Takashi; Sotozono, Chie
Abstract: Purpose: To evaluate the toxicity of Amphotericin B (AmB) in Optisol™-GS Corneal Storage Media (Bausch & Lomb) on corneal epithelial cell (CEC) morphology and migration ability. Methods: Sclerocorneal strips were removed from male Japanese white rabbits, and then stored at 4 °C in Optisol™-GS containing 0 µg/ml of AmB (control group) and 2.5, 5, 25, and 50 µg/ml of AmB (AmB groups; four eyes per group). After 7 days of storage, CEC morphology was evaluated by hematoxylin-eosin staining, immunohistochemical staining (ZO-1), and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Moreover, to evaluate CEC migration ability, three corneal blocks (6–8 × 3 mm each) from one preserved cornea were cultured for 24 h, and the area of CEC migration (2 mm at the central region) onto the stromal surface was then measured. Results: At 5, 25, and 50 µg/ml of AmB, deformation and vacuolation of CECs were observed in all preserved corneas. ZO-1 expression was significantly reduced in corneas preserved at AmB concentrations of 25 and 50 µg/ml. TUNEL Labeling Index was significantly increased at AmB concentrations of ≥5 µg/ml. CEC migration was inhibited in a dose-dependent manner at AmB concentrations of 25 and 50 µg/ml compared to the control group. Conclusions: The addition of AmB to Optisol™-GS can be toxic to CECs and inhibit their migration at a concentration of ≥5 µg/ml. AmB at a concentration of 2.5 µg/ml can be considered safe for the preservation of donor corneal tissue used in corneal epithelial transplantation surgery.